A Comparative Study on the Effects of Spinal Versus General Anaesthesia on Apgar Score of the Neonates among Patients Enduring Elective Caesarean Section - Muhammad Nadeem Khan, Hina Zubair, Sara Akram, Saima Perveen, Arooj Fatima, Madiah (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this analysis was to do the comparison of the effect of general anesthesia and spinal anesthesia on neonatal Apgar score in patients enduring elective cesarean section. Study design: A Randomized control trial. Place and duration: In the department of Anesthesia, pain and intensive care Divisional Headquarters teaching Hospital Mirpur Hospital for six-months duration from July 2021 to December 2021. Methods: In this study, 120 patients in the cesarean section operating room list were alienated into 2 equal groups. Group I (n = 60) were given spinal anesthesia and in group II (n = 60), general anesthesia was given. There was no significant difference in height, weight and age of patients. Patient information is recorded on the designed performa. Comparisons were made between groups I and II. Apgar scores were assessed 1 and 5 minutes after birth and recorded as proforma. Results: The patients mean age of the group-I was 30.04 ± 4.9 years and 29.81± 5.84 years in the group-II. The mean change between the groups was not statistically substantial (p = 0.66). The patients mean weight in the first group was 70.95 ± 10.31 kg and in the second group it was 73.50 ±11.28 kg. Infants born to women who received spinal anesthesia had a higher Apgar score at 1 minute and 5 minutes compared to females who were given general anesthesia (P <0.001). The highest proportion of patients in the first group exhibited better Apgar score than patients in the second group. Conclusion: Neonates of females who had cesarean section under spinal anesthesia had better APGAR score than under general anesthesia.